THE LATIHAN SKIPPING DENGAN TEKNIK HIGH STEP MENINGKATKAN TINGGI LONCATAN PEMAIN BOLA BASKET - I.G.A Sri Wahyuni Novianti; I Made Niko Winaya; Ni Wayan Tianing (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
This study aims to determine the skipping exercise with high step technique to increase men basketball player vertical jump in junior high school 1 Denpasar. This research method is pre–experimental which used one group pre-test and post-test group design conducted in May to June 2014 where the population of this study was students in junior high school 1 Denpasar who follow the basketball extracurricular , they were at the age of 12–15 (mean 13.2±0.616) years old. Sampling technique in this study is purposive sampling with a sample of 20 people. The sample joined to do skipping exercise with high step technique for 4 weeks which was 3 times a week. The results the of study by using the paired sample t-test showed that the mean increase in vertical jump before and after exercise showed p=0.000 (p <0.05) mean difference 7.25±1.06. The conclusion is skipping exercise with high step technique significantly increase the vertical jump among basketball player by 1.97%.